1990
DOI: 10.1055/s-2007-998144
|View full text |Cite
|
Sign up to set email alerts
|

Der Borrelien-Titer bei HNO-Erkrankungen*

Abstract: In 139 patients with facial paralysis, sudden hearing loss, vertigo, and lymphadenitis of the head and neck, the prevalence of borrelia burgdorferi serum antibodies was examined with the help of immunofluorescence assays for IgG- and IgM-antibodies, immunofluorescence assays after absorption of cross-reacting antibodies with treponema phagedenis, ELISA, and Western Blot. Six out of 22 patients with facial paralysis, 11 out of 72 with hearing loss, eight out of 45 with vertigo, and five out of 25 with lymphaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
2
1
0
Order By: Relevance
“…The prevalence of seropositivity against B. burgdorferi in over 2000 patients with vertigo in our Department was 2%, which is at the same level as the prevalence of seropositivity in the normal Finnish population [25]. In accordance with our results, some previous studies have shown a connection between sudden SHL and the presence of positive levels of antibodies against B. burgdorferi [8,10,22,31]. If not supported by other positive laboratory findings or typical clinical signs, a positive serological finding alone does not confirm the causal relationship between sudden SHL and LB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of seropositivity against B. burgdorferi in over 2000 patients with vertigo in our Department was 2%, which is at the same level as the prevalence of seropositivity in the normal Finnish population [25]. In accordance with our results, some previous studies have shown a connection between sudden SHL and the presence of positive levels of antibodies against B. burgdorferi [8,10,22,31]. If not supported by other positive laboratory findings or typical clinical signs, a positive serological finding alone does not confirm the causal relationship between sudden SHL and LB.…”
Section: Discussionsupporting
confidence: 91%
“…LB seems to affect the cochlear part of the nerve more often [31], but the vestibular part can also be involved [10,25]. Reik [30] has reported the occurrence of sudden SHL in patients with both early and late LB.…”
Section: Introductionmentioning
confidence: 99%
“…With the aim to prevent long term sequels of facial palsy, in the present study acoustic refl ex values and HB scale score were assessed as prognostic indicators of facial palsy in neuroborreliosis. Borreliosis was present in 35 (19.88%) of 176 patients with facial palsy, which is consistent with literature data, where its inci-dence ranges from 7.1% to 41% 3, [14][15][16] . However, the body of data on its incidence is rather scarce, the more so as a higher percentage of facial palsy in borreliosis is reported in pediatric population.…”
Section: Discussionsupporting
confidence: 91%